"Not your ordinary guidebook": gender and the redefinition of the nineteenth-century guidebook. Issue 2 (3rd April 2019) - Proteau, Jasmine
ABSTRACT: Problematising the definition of a travel guidebook in the context of the nineteenth century, this study offers a framework for the improvement of guidebook identification and analysis. Through redefinition, it seeks to include works which have been either missed or miscategorised in the larger body of travel literature, paying particular attention to those written by women. The aim of this essay is twofold: first, it offers a new definition and set of parameters through which we can analyse the nineteenth-century guidebook; second, it seeks to establish women and gender into the historiography of the guidebook by showing that women were active in the production of different guidebook subgenres in the nineteenth century. This work better equips scholars in the study of guidebooks, and by examining female-authored guides, highlights the need for greater investigation into women's production and consumption of the nineteenth century's most important tool for travel.